Respuesta :

Answer: (1, -3)

Step-by-step explanation:

[tex]8x+4y=-4\\-4x-5y=11[/tex]

[tex]2(-4x-5y)=11(2)\\-8x-10y=22[/tex]

new system:

[tex]8x+4y=-4\\-8x-10y=22[/tex]

add.

[tex]-6y=18\\y=-3[/tex]

plug in -3 for y

[tex]8x+4(-3)=-4\\8x-12=-4\\8x=8\\x=1[/tex]

system:

[tex](1,-3)[/tex]

Answer:

  • Make one of the variable in one of the equations the subject of the formular first.
  • [tex]4y = - 4 - 8x[/tex]
  • to leave y independent divide the whole equation by the coefficient of y at this point it is 4.Then divided the whole equation by 4.
  • [tex] \frac{4y}{4} = \frac{ - 4}{4} - \frac{8x}{4} [/tex]
  • therefore the new equation will be
  • [tex]y = - 1 - 2x....(3)[/tex]
  • substitute the new equation in the other equation N.B not the one you extracted the new equation from.
  • you will use -4x-5y=11 in substituting y=-1-2y
  • [tex] - 4x - 5( - 1 - 2x) = 11 \\ - 4x + 5 + 10x= 11 \\ \\ - 4x + 10x = 11 - 5 \\ 6x = 6 \\ \frac{6x}{6} = \frac{6}{6} \\ x = 1[/tex]
  • [tex]y = - 1 - 2(1) \\ y = - 1 - 2 \\ y = - 3[/tex]
  • HOPE THIS HELPS!